Historical Review of Gebang Tinatar Tegalsari Pesantren and its Genealogy Relationship with Kediri's Pesantren - Moh Ashif Fuadi (IAIN Syekh Nurjati Cirebon, 2022)
Indonesia has thousands of the oldest educational institutions, namely pesantren. According to Dutch Indonesianist Martin van Bruinessen, the first pesantren institutionally was pesantren Tegalsari Ponorogo. The pesantren was founded by Kiai Ageng Muhammad Besari but experienced its heyday in the 19th century by Kiai Hasan Besari, the grandson of the founder of pesantren. Along with the dynamics of the ups and downs of Pesantren Tegalsari, the line of the intellectual struggle of pesantren continued by its descendants such as Pondok Modern Gontor and Pesantren al-Islam Joresan. Interestingly, there is an even further genealogical relationship between the popular salaf pesantren in Kediri, namely Pesantren Lirboyo, Ploso, Jampes and Bendo, which have thousands of students. This research will reveal the historical study of Pesantren Tegalsari and its genealogical relationship or relationship with the pesantren-pesantren. Through the approach of literature studies, observations and interviews, this study concluded that there is a genealogical relationship between the four popular pesantren through the descendants of the Kiai Mesir Durenan Trenggalek taken by the son-in-law by the Tegalsari breed. So, the offspring between four pesantren at Kediri and Tegalsari connected with Tegalsari Pesantren through the path of women (wives). Kiai Mesir itself is the son of Kiai Yahuda, a Ulama from Lorok Pacitan.